2013
DOI: 10.1074/jbc.m113.480830
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Neutralization Mechanism of Monoclonal Antibody 6C2 against Ricin

Abstract: Background:The antibody 6C2 exhibited an unusually potent neutralizing ability against ricin. Results: We determined the crystal structure of 6C2 Fab in complex with RTA and mapped the epitope on RTA. Conclusion: The binding of 6C2 hinders the interaction between RTA and the ribosome, thus inhibiting the activities of RTA. Significance: Our findings further confirm the role of ribosomal elements in ricin activity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In addition, CDR3 generates six hydrogen bonds to RTA with one crucial hydrogen bond between CDR3 residue Ser 98 and RTAs Thr 116 in β-strand H and the most prominent interaction occurring between CDR3 and α-helix B (residues 97–107) that forms two of the six hydrogen bonds. This interaction results in the burial of 472 Å 2 and, importantly, involves hydrogen bonding between CDR3 residue Arg104 and RTA residue Thr105 (Figure 4A), a residue within α-helix B that we have predicted is a common contact point among a number of very potent ricin toxin-neutralizing murine mAbs 15; 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CDR3 generates six hydrogen bonds to RTA with one crucial hydrogen bond between CDR3 residue Ser 98 and RTAs Thr 116 in β-strand H and the most prominent interaction occurring between CDR3 and α-helix B (residues 97–107) that forms two of the six hydrogen bonds. This interaction results in the burial of 472 Å 2 and, importantly, involves hydrogen bonding between CDR3 residue Arg104 and RTA residue Thr105 (Figure 4A), a residue within α-helix B that we have predicted is a common contact point among a number of very potent ricin toxin-neutralizing murine mAbs 15; 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on differential peptide reactivity, we postulate that R70 and PB10 contact residues Q98, E99, E102, T105 and H106 (Table S2; Figure S3). Another R70/PB10-like murine mAb, 6C2, was recently described 12 and the X-ray crystal structure solved of its Fab fragments in complex with RTA [ PDB: 4KUC ] 26 . The crystal structure revealed that 6C2 is virtually identical to R70/PB10 in that it makes key contacts with RTA at residues Gln98, Glu99, Glu102, and Thr105.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ricin-neutralizing antibody 6C2 recognizes an epitope distinct from the catalytic active site of RTA and is more potent in its neutralizing ability relative to antibodies that bind the active site (Dai et al , 2011). These researchers further proposed that this antibody may inhibit binding of RTA to the ribosome (Zhu et al , 2013). We show here for the first time that targeting specific arginine residues of RTA can reduce its toxicity in mammalian cells by inhibiting its interactions with the ribosome while leaving the active site intact.…”
Section: Discussionmentioning
confidence: 99%
“…High resolution epitope mapping studies using a phage displayed peptide library demonstrated that PB10 and R70 recognize slightly different epitopes, even though they are focused on the same α-helix and bind the same peptide [101]. Recent X-ray crystallographic studies of toxin-antibody complexes have enabled atomic level resolution of epitopes within Cluster I. Zhu et al solved the structure of RTA in complex with Fab fragments from a PB10-like mAb called 6C2 [102], which revealed antibody contact primarily with α-helix B (residues 97–107).…”
Section: G Establishing Surrogate Markers Of Immunity To Ricinmentioning
confidence: 99%
“…In addition, a non-human primate study with RiVax demonstrated the vaccine’s potential to elicit immunity to aerosolized ricin challenge [47]. Finally, the first atomic level insights into the nature of neutralizing B cell epitopes on RTA emerged [97,102]. …”
Section: H Expert Commentary and Five-year Viewmentioning
confidence: 99%